Psychiatry as a Human Science : Phenomenological, Hermeneutical and Lacanian Perspectives. - Mooij, Antoine (Contemporary psychoanalytic studies., 2012)
Psychiatry or psychopathology finds itself in a state of imbalance. The reason: the impossibility to unite biological and psychological factors. Effectively, this leads to the psychic reality being largely ignored. And yet psychiatry as a human science wi.